Transcription coactivator peroxisome proliferator-activated receptor-binding protein/mediator 1 deficiency abrogates acetaminophen hepatotoxicity - Jia, Yuzhi (National Academy of Sciences, 2005)
Peroxisome proliferator-activated receptor-binding protein (PBP), also known as thyroid hormone receptor-associated protein 220/vitamin D receptor-interacting protein 205/mediator 1, an anchor for multisubunit mediator transcription complex, functions as a transcription coactivator for nuclear receptors. Disruption of the PBP gene results in embryonic lethality around embryonic day 11.5 by affecting placental and multiorgan development. Here, we report that targeted deletion of PBP in liver parenchymal cells (PBP(Liv-/-)) results in the abrogation of hypertrophic and hyperplastic influences in liver mediated by constitutive androstane receptor (CAR) ligands phenobarbital (PB) and 1,4-bis-[2-(3,5-dichloropyridyloxy)]benzene, and of acetaminophen-induced hepatotoxicity. CAR interacts with the two nuclear receptor-interacting LXXLL (L, leucine; X, any amino acid) motifs in PBP in a ligand-dependent manner. We also show that PBP interacts with the C-terminal portion of CAR, suggesting that PBP is involved in the regulation of CAR function. Although the full-length PBP only minimally increased CAR transcriptional activity, a truncated form of PBP (amino acids 487-735) functioned as a dominant negative repressor, establishing that PBP functions as a coactivator for CAR. A reduction in CAR mRNA and protein level observed in PBP(Liv-/-) mouse liver suggests that PBP may regulate hepatic CAR expression. PBP-deficient hepatocytes in liver failed to reveal PB-dependent translocation of CAR to the nucleus. Adenoviral reconstitution of PBP in PBP(Liv-/-) mouse livers restored PB-mediated nuclear translocation of CAR as well as inducibility of CYP1A2, CYP2B10, CYP3A11, and CYP7A1 expression. We conclude that transcription coactivator PBP/TRAP220/MED1 is involved in the regulation of hepatic CAR function and that PBP deficiency in liver abrogates acetaminophen hepatotoxicity.